2008
DOI: 10.1007/s10832-008-9468-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrical, optical, and structural properties of ITO co-sputtered IZO films by dual target magnetron sputtering

Abstract: We have investigated electrical, optical, and structural properties of indium tin oxide (ITO) co-sputtered indium zinc oxide (IZO) film prepared by a dual target direct current (DC) magnetron sputtering at room temperature in pure Ar ambient. It was shown that the resistivity and sheet resistance of ITO co-sputtered IZO films monotonically increased with increasing DC power of ITO target at constant DC power of IZO target. Synchrotron X-ray scattering and scanning electron microscope examination results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Many groups have reported the influence on ZnO thin films of metal dopants, including In [10], Al [11][12][13][14], Fe [12,15], Mn [16], Mg [17], and Ga [12,18], to replace indium-doped tin oxide or fluorine-doped tin oxide [1,3]. One promising dopant is Cu, which has been reported to show enhanced properties such as higher conductivity [19], diluted magnetic properties [15], and improved crystal quality [20].…”
Section: Introductionmentioning
confidence: 99%
“…Many groups have reported the influence on ZnO thin films of metal dopants, including In [10], Al [11][12][13][14], Fe [12,15], Mn [16], Mg [17], and Ga [12,18], to replace indium-doped tin oxide or fluorine-doped tin oxide [1,3]. One promising dopant is Cu, which has been reported to show enhanced properties such as higher conductivity [19], diluted magnetic properties [15], and improved crystal quality [20].…”
Section: Introductionmentioning
confidence: 99%
“…The study found that Al doping increased the electrical conductivity of the ITO films due to the formation of oxygen vacancies, which enhanced the carrier concentration and mobility. However, the study also revealed that excessive Al doping could result in a decrease in the optical transmittance of the ITO films, which could limit their transparency for certain applications [12]. A study investigated the mechanical and electrical properties of ITO thin films on flexible substrates.…”
Section: Related Workmentioning
confidence: 99%
“…TCO films have been utilized in various optoelectronic applications due to their exceptional optical transmittance (>80%) in the visible wavelength range (380-700 nm) and favorable electrical properties (resistivity of <10 −4 Ω.cm). These applications include thin-film transistors, solar cells, organic light-emitting diodes (OLEDs), flat-panel displays, liquidcrystal displays, and plasma display panels [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Various techniques such as pulsed laser deposition, thermal evaporation, chemical vapor deposition, electron-beam evaporation, sol-gel deposition, ion beam-assisted deposition, and magnetron sputtering are utilized for depositing TCO films [3,4,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%